The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10623-018-0537-7
|View full text |Cite
|
Sign up to set email alerts
|

An Erdős-Ko-Rado theorem for the group $$\hbox {PSU}(3, q)$$ PSU ( 3 , q )

Abstract: In this paper we consider the derangement graph for the group PSU(3, q) where q is a prime power. We calculate all eigenvalues for this derangement graph and use these eigenvalues to prove that PSU(3, q) has the Erdős-Ko-Rado property and, provided that q = 2, 5, another property that we call the Erdős-Ko-Rado module property.2010 Mathematics Subject Classification. Primary 05C35; Secondary 05C69, 20B05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Once we define canonical cocliques (or cliques), we can discuss the EKR properties of G after identifying G with Γ(G). The EKR-module property was first formally defined by Meagher [21] in this context: a permutation group G naturally acts on the vector space W spanned by the characteristic vectors of canonical cliques, which makes W a G-module.…”
Section: Ekr-type Resultsmentioning
confidence: 99%
“…Once we define canonical cocliques (or cliques), we can discuss the EKR properties of G after identifying G with Γ(G). The EKR-module property was first formally defined by Meagher [21] in this context: a permutation group G naturally acts on the vector space W spanned by the characteristic vectors of canonical cliques, which makes W a G-module.…”
Section: Ekr-type Resultsmentioning
confidence: 99%
“…A transitive group is said to satisfy the EKR-module property if the characteristic vector of every maximum intersecting set is a linear combination of the characteristic vectors of cosets of stabilizers of points. This generalization of the wellknown permutation group version of the Erdős-Ko-Rado (EKR) theorem was introduced by K. Meagher in [28]. In this article, we present several infinite families of permutation groups satisfying the EKR-module property, which shows that permutation groups satisfying this property are quite diverse.…”
mentioning
confidence: 89%
“…the characteristic vector of the canonical intersecting set gG α , which we call a canonical vector for convenience. The next definition was first introduced in [28].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Spiga showed that the maximum intersecting sets of PGL n+1 (q) acting on the points of the projective space P n q are the cosets of the stabilizer of a point and the cosets of the stabilizer of a hyperplan [15]. For more studies, we refer the reader to [7,11,14].…”
Section: Introductionmentioning
confidence: 99%